Peoples and Crafts in Period IVB at Hasanlu, Iran. - de Schauensee, Maude.
1 online resource (249 pages)
Keywords: This volume describes a series of ongoing research projects from the site of Hasanlu, providing new information on Iron Age technology. Topics covered range from crafts such as textiles, glassmaking, metallurgy, and weapon making, to DNA research on the population history of the area.